Infinity warps two-in-one ebook - Acker, Ben (Infinity Wars: Infinity Warps (2018)., 2019)
Collects Infinity Wars: Soldier Supreme #1-2, Infinity Wars: Iron Hammer #1-2, Infinity Wars: Arachknight #1-2, Infinity Wars: Weapon Hex #1-2, Infinity Wars: Ghost Panther #1-2 And Infinity Wars: Infinity Warps #1-2. Requiem has used the Infinity Stones to cut the universe's population in half — but not by killing anyone. As reality itself warps, Earth's heroes find themselves…merged together! Stephen Rogers couldn't serve his country in World War II — until a sorcerous government program transformed him into the Soldier Supreme! Stark Odinson, kidnapped by Ice Giants and forced to make weapons, turned their forges against them and became Iron Hammer! A sinister deal turned Wakandan prince T'Challa into the Ghost Panther! Plus: More uncanny twists on your favorite Marvel heroes! The Arachknight! Weapon Hex! The Terrific Two! Green Widow! Moon Squirrel and Tippysaur! Diamond Patch! Kamala Kang! And the Punisher Pack!